Asset Scale and Capital Structure on The Performance of Sharia Banks - Rizky Windar Amelia; Cahaya Nugrahani (Postgraduate Program Merdeka University, 2018)
The purpose of this study is to examine the effect of operation scale and capital structure on the performance of Sharia Banks - Sharia Business Units and Sharia BPR in Central Java and Yogyakarta Special Region. The level of performance is obtained through annual publication financial report in which the banking health ratio is measured through the criteria regulated by Bank Indonesia using five aspects of CAMEL, capital adequacy ratio, asset quality, management, earning, and liquidity aspects. The number of bank samples studied consisted of 15 sharia banks, sharia business units and 19 Sharia BPRs in Central Java and Yogyakarta Special Region using financial statements on December 31, 2015. The model tests were carried out using Pearson Product Moment and One-Way ANOVA tests. The test results explain there is a significant influence between the asset scale and capital structure on the performance of sharia banking operations. DOI: https://doi.org/10.26905/afr.v1i2.2789